Higher-power supercapacitor electrodes based on mesoporous manganese oxide coating on vertically aligned carbon nanofibers1. Issue 18 (14th May 2015) - Klankowski, Steven A.; Pandey, Gaind P.; Malek, Gary; Thomas, Conor R.; Bernasek, Steven L.; Wu, Judy; Li, Jun
<x xml:space="preserve">Abstract</x> A study on the development of high-power supercapacitor materials based on formation of thick mesoporous MnO2 shells on a highly conductive 3D template using vertically aligned carbon nanofibers (VACNFs).